Development of dynamic gas generation system for ultratrace amounts of acetone at parts-per-trillion levels with low temperature permeation method - Reiji Aoyagi; Takahiro Arakawa; Kenta Iitani; Kohji Mitsubayashi; Yoshika Sekine; Yuichiro Kaifuku (Discover Applied Sciences)
Abstract Different types of gas sensing devices have been developed to monitor trace amounts of volatile compounds emitted from exhalation, human skin, building materials, and atmospheric chemical reactions, etc.. In particular, the recent progress in transdermal sensing techniques could enable detection of trace amounts of biochemicals at parts per trillion (ppt) levels. Preparation of known-concentration gases at that level is very important to accurately evaluate and calibrate these sensing devices. We developed an accurate dynamic gas generation system with a permeation method at the ppt level for acetone, a well-known biomarker of diabetes and obese, which consists of an accurately low-temperature controlled tube chamber with a thermostat, mass flow controller, custom-built acetone permeation tube with a low permeability, and nitrogen carrier gas. With the system, the permeation rate of acetone was 0.409 ± 0.011 ng min−1 (k = 2). The calculated concentrations obtained from the permeation rate and three setting points of the carrier gas flow rate (20.26, 38.26, and 74.86 pptv) agreed with those analyzed by the dinitrophenylhydrazine derivatization–high-performance liquid chromatography method (20.33, 37.85, and 81.08 pptv) within the level of each expanded uncertainty of 3.0–5.1%. The temperature dependence of the permeation tube obeyed an Arrhenius-type law. The error related to temperature change in the permeation rate in the system was estimated to be below 0.1% of the permeation rate. This study demonstrates an accurate gas preparation with an ultratrace amount of acetone gas using the dynamic low temperature permeation method.